Robert. E. Howard, the American Frontier, and Borderlands in the Stories of Conan the Barbarian. Issue 3 (January 2016) - van Duinen, Jared
Abstract : Much has been written about the influence of the American frontier on Robert E. Howard and how this can be seen in his writings. An interesting focus for some of this work has been Frederick Jackson Turner's frontier thesis and, more specifically, Richard Slotkin's critique and reworking of this "frontier myth." This article suggests that another critique of Turner's thesis, that of Herbert Eugene Bolton's borderlands theory, also offers a fruitful interpretative framework through which to view the Conan stories. To this end, it analyses specific Conan tales, with a particular focus on "Beyond the Black River, " to explore the ways in which the world of Conan exhibits borderlands traits. It concludes with some reflections on the implications this might have for the inception of the sword and sorcery genre more generally.